Shopfloor matters : labor-management relations in twentieth-century American manufacturing - Fairris, David, 1955- (Routledge studies in business organization and networks, 1997)
This book offers not only a comprehensive analysis of the changing nature of shopfloor labor-management relations in the large firms of this century, it also supplies empirical evidence of the effect of changes on productivity.